Pengaruh Model Tumpangsari dan Pengaturan Jarak Tanam Kacang Nasi (Vigna angularis L.) Kultivar Lokal terhadap Pertumbuhan dan Hasil Tanaman Jagung (Zea mays L.) - Fransiskus Xaverius Neo; Syprianus Ceunfin (Savana Cendana, 2018)
Maize and bean crops are two types of plants suitable for intercropping. The objective of this research is 1) growth and yield of maize in intercropping cropping pattern; 2) the best intercropping models in improving the growth and yield of maize; and 3) good plant spacing arrangement in cropping pattern of intercropping of maize and rice beans. The experiment was conducted in experimental garden of Fakultas Pertanian, Universitas Timor from December 2016 until March 2017. All treatments of the plot experiment were arranged in a Factorial Randomized Completely Block Design (RAK) 3 × 2 + monoculture with three replicates Treatment, the first factor is intercropping models consisting of three levels: interspace intercropping; and Salome intercropping; Alternative intercropping and the second factor is the arrangement of maize cropping spacing: Single row; Double row. The results showed the interaction between intercropping model and plant spacing arrangement to observation parameter of dry seed weight per plot, dry weight of seed per hectare. Maize crops intercropped with rice beans in the treatment of intercropping model of Salome with arrangement spacing double row resulted in the highest dry weight of seeds per plot of 269.31 g and 0.89 t / ha.